Batch files to go : a programmer's library - Richardson, Ronny (Blue Ridge Summit, PA : Windcrest, 1992)
This collection of ready-to-use batch files features more than 100 keystroke-saving programs. It presents a complete set of fully-developed programs - all available on disk for instant access - which can be used as they are or altered to handle virtually any file management task.
Why program?; batch file command glossary; customizing your system; working with DOS commands; new DOS commands; simple menus; complex menus; using colour and sound; making your system secure; energizing batch files; interactive batch files; enhancing your batch files.
Includes index.
Keywords: ELECTRONIC DATA PROCESSING -- BATCH PROCESSING